STUDI PERBAIKAN SISTEM PEMBUMIAN UNTUK MENCEGAH KEGAGALAN LIGHTNING ARRESTER PADA PENYULANG SULAHAN BANGLI - Julyantara, I Nyoman; Janardana, I Gusti Ngurah; Dyana Arjana, I Gede (Jurnal SPEKTRUM; Vol 6 No 4 (2019): Jurnal SPEKTRUM, 2019)
The Feeder of Sulahan Bangli is located in the highlands which are often exposed to natural phenomena in the form of lightning, so the Feeder of Sulahan Bangli often experience interference with over voltage. Lightning Arrester in The Feeder of Sulahan Bangli often experience failure due to overvoltages during lightning surges. In 2016 there were 4 times the overvoltage failure in conventional Lightning Arrester in The Feeder of Sulahan (PT. PLN (Pesero) UP3 East Bali, 2016). The failure of Lightning Arrester in The Feeder of Sulahan Bangli is caused by the interference of backback-flashover, this is caused by the earth resistance value in Lightning Arrester exceeds the standard value <1 ? which is an average of 8 ? so that it needs to be repaired grounding system. In this study an analysis of the area of the grounding system is installed, analyzing the various grounding systems that are suitable in the Feeder of Sulahan, and calculating the cost of each grounding system. The results of calculations and analysis of several grounding systems used by the Grid-Rod grounding system in wet and clay soils are the most optimal type of groundinging system that can be used as a reference for improving the grounding system in The Feeder of Sulahan Bangli with an earth resistance value of 0, 4543 Ohms at a cost of Rp. 5,416,625, - per unit and on a 0.4461 Ohm thick clay soil at a cost of Rp. 8,728,125, - per unit.